Transfer of Arsenic from Groundwater and Paddy Soil to Rice (Oryza sativa L.) Grain: A Micro Level Study in Chandina, Comilla - Rahman, Md. Habibur; Farazi, Md. Mohashin; Begum, Kohinoor; Islam, Md. Serazul (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Rice (Oryza sativa L.) is one of the major food crops in many countries. As the cultivation of rice requires huge volume of water, long term use of Arsenic contaminated groundwater for irrigation may result in the increase of arsenic concentration in the agricultural soil and eventually accumulation in rice grains. A micro level study was conducted to investigate the transfer of arsenic from irrigation water and soil to rice plants in the arsenic affected 8 unions of Chandina upazilla, Comilla district. The level of arsenic in irrigation water (0.12±0.08 and 0.67±0.07 mg l-1) was much above the WHO permissible limit of 0.01 mg l-1 for drinking water and FAO permissible limit of 0.10 mg l-1 for irrigation water. The total soil arsenic concentrations ranged from 3.21±0.80 to 8.74±2.83 mg kg-1 dry weight of soil, which was below the maximum acceptable limit for agricultural soil of 20.0 mg kg-1 as recommended by the European Community. The accumulation of arsenic in the grain ranged from 0.12±0.04 to 0.58±0.06 mg kg-1 in Boro and 0.16±0.04 to 1.06±0.20 mg kg-1 in T. Aman. Except grain sample (T. Aman) of one union, the grains in both Boro and T. Aman of all unions did not exceed 1.0 mg kg-1 dry weight of arsenic (the permissible limit of arsenic in rice according to WHO recommendation). Thus, till now rice has remained harmless for consumption in the study area. The results clearly showed that the arsenic content in the grains of Boro rice is correlated to the intensity of arsenic contamination of irrigation water and soil. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) 74-82 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>